Keterlibatan dan Partisipasi Masyarakat dalam Mitigasi Bencana Banjir: Studi Kasus Kabupaten Sidenreng Rappang, Indonesia - Muliani Samiri; Andi Nilwana; Nurjannah Nonci; Jamaluddin Ahmad; Fitriani Fitriani (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2024)
This study evaluates community participation in flood disaster mitigation efforts in Wetee Village, Sidenreng Rappang Regency. Employing a descriptive qualitative approach, data were gathered through structured observations and in-depth interviews with community members and officials responsible for disaster management. The interview data were subsequently analyzed using NVivo 12 Plus software. The study focuses on community empowerment strategies implemented by the Sidenreng Rappang Regional Disaster Management Agency, using an eight-step community participation model to assess engagement levels. Findings reveal that the community’s involvement in flood mitigation remains largely at a quasi-participation level, characterized by limited engagement in planning and supervisory processes. This restricted level of participation is seen to hinder the overall effectiveness of disaster mitigation initiatives. The study recommends promoting community participation from pseudo-participation to a ‘delegated power’ level to improve outcomes, facilitating comprehensive involvement in planning, execution, and oversight. These findings underscore the critical role of collaborative efforts across various stakeholders to enhance disaster preparedness and response capacities at the local level, ultimately fostering a more resilient community.